EVALUATION PHYSICAL QUALITY AND TENDERNESS OF BALI DUCK (Anas sp) FROM MARINATE ROSELLA FLOWER EXTRACT (Hibiscus sabdariffa Linn) - Y.C., Bani; Umiarti, A. T.; Okarini, I. A. (Jurnal Peternakan Tropika, 2022)
Duck is one of the livestock that produces meat which is a source of animal protein that can be utilized by the community. This study aimed to evaluate the physical quality and tenderness the meat of male Bali duck ( Anas sp ) marinate used rosella flower extract ( Hibiscus sabdariffa Linn ). This research was conducted in November-December 2021 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The exeperimental design used was a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The four treatments included: (P0) male Bali duck meat without rosella flower extract as a control, (P1) male Bali duck meat marinated with 5% rosella flower extract, (P2) male Bali duck meat marinated with 10% rosella flower extract, (P3) male Bali duck meat was marinated with 15% and the marination time was 60 minutes. The variables observed included the degree of acidity (pH), the percentage of cooking loss, color, and tenderness. The results of this study indicate that the marination of rosella flower extract to 15% obtained an average value of acidity (pH) 4,27-6,02, cooking loss percentage 38,74-41,34%, color brigthness (L*) 22,24-25,65, reddish color (a*) 8,36-11,54, yellowish color (b*) 12,67-15,70, and acceptance of tenderness 4,93-7,33. The conclusion of this study that the marination of rosella flower extract up to 15% had a significant effects (P<0,05) on the degree of acidity (pH), the cooking loss percentage, the yellowish color (b*), and the acceptance of tenderness, while the brightness (L*) and the reddish color (a*) showed non-significant effect (P>0,05) on male Bali duck meat ( Anas sp ).   Keywords: rosella flowers, duck meat, marinate